Penggunaan Media Konkret pada Materi Bangun Ruang Sebagai Upaya Meningkatkan Hasil Belajar Matematika Siswa Sekolah Dasar - Evi Yuanita; Elok Izzatul Jannah; Iis Mutaqwiati; Prinda Tata Arsinta; Salsabilla Aura Putri Islami; Chici Erni Agustini (Prosiding Konferensi Ilmiah Dasar, 2026)
Learning three-dimensional shapes in elementary schools remains challenging because the concepts are abstract, making it difficult for students in the concrete operational stage to understand the properties and elements of geometric solids. This study aims to describe the concepts and characteristics of concrete media, analyze their benefits, and examine their influence on students' conceptual understanding and mathematics learning outcomes in learning three-dimensional shapes. This study employed a qualitative descriptive approach using a literature review. Data were collected from scientific journals, conference proceedings, classroom action research reports, and relevant reference books, and were analyzed using content analysis supported by source triangulation. The findings indicate that concrete media, such as cardboard boxes, cans, and balls, help students understand three-dimensional shapes through direct observation and object manipulation. In addition, the use of concrete media increases students' motivation, active participation, spatial visualization skills, and mathematics learning outcomes. Therefore, concrete media can be considered an effective learning strategy that supports elementary school students in understanding abstract mathematical concepts.